2005
DOI: 10.1080/11038120510031734
|View full text |Cite
|
Sign up to set email alerts
|

Assistive devices in activities of daily living used by persons with age-related macular degeneration: A population study of 85-year-olds living at home

Abstract: The purpose of this study was to investigate the overall use of assistive devices among persons with age-related macular degeneration (ARMD) and how it is related to dependence in daily activities. This was a retrospective, descriptive, cross-sectional population study of 85-year-olds. The most common category of assistive devices was bathing devices followed by mobility devices. The overall use of assistive devices was 82%, and around 80% of the device users were independent in activities of daily living. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…These articles investigated the use of assistive devices and their relation to dependence in daily activities among 85-year-olds with age-related macular degeneration (26), the ability to perform ADL, received home adaptations, possession of assistive devices, and perceived health and morale with and without hip fractures was also studied (27), the association between everyday satisfaction and social relations, continuity, self-determination, and use of own resources among 85-year-olds with physical disabilities was investigated (37), the association between interests and functional ability, self-related health, and sociodemographic characteristics of people aged 86 living at home (38), and the personal meaning of ageing and well-being from the perspective of community-dwelling women over 85 years of age (39).…”
Section: Research About the Oldest Oldmentioning
confidence: 99%
See 1 more Smart Citation
“…These articles investigated the use of assistive devices and their relation to dependence in daily activities among 85-year-olds with age-related macular degeneration (26), the ability to perform ADL, received home adaptations, possession of assistive devices, and perceived health and morale with and without hip fractures was also studied (27), the association between everyday satisfaction and social relations, continuity, self-determination, and use of own resources among 85-year-olds with physical disabilities was investigated (37), the association between interests and functional ability, self-related health, and sociodemographic characteristics of people aged 86 living at home (38), and the personal meaning of ageing and well-being from the perspective of community-dwelling women over 85 years of age (39).…”
Section: Research About the Oldest Oldmentioning
confidence: 99%
“…Studies have been performed concerning life experience and adjustment (20), loneliness, social and family contacts, purpose in life and religiousness (21), well-being (22) morale and health (23,24) inner strength, resilience, sense of coherence, purpose in life, and self-transcendence (3), care trajectories (5) or pathways through formal service (25), activities of daily life comparing levels of dependence between different groups of elderly, both between different illnesses (26,27) and different places of residence (21). Other areas studied in this age group are activity patterns (28), interests (29), occupational engagement and life satisfaction (30), technology (31), and use of assistive devices (26,29).…”
Section: Research About the Oldest Oldmentioning
confidence: 99%
“…Articles solely about the oldest old thus seem rare despite the fact that this is the group of elderly that is increasing fastest in most societies (7). However, as three of the five articles including only people over 85 were published in 2005 and 2006 (44,50,51) an increased interest in research with this age group might be expected. Occupational therapy has an important role in engaging the elderly in meaningful activities adapted to the changing abilities that follow with higher ages (67).…”
Section: Elderly People Present In the Researchmentioning
confidence: 92%
“…Seventy of the articles (33%) had an age spread that started below 50 years of age (see for example (46,47)). About one-third of the articles (62/29%) had respondents who were all over 65 years of age (see for example (48,49)) and five of these articles included only respondents over 85 years of age (2% of total articles, (19,42,44,50,51)). There were 24 (11%) articles only giving a mean (which had to be over 60 to be included) and there was also a group of articles (12/6%) that denominated the respondents as elderly care, older people, demented elderly, middle age and older, older adults, 20% over retirement age etc.…”
Section: Age Groups Includedmentioning
confidence: 99%
“…33,34 Occupational therapists are actively involved in the prescription and education of assistive technology. 35 While there has been some debate about its usage, Gitlin et al 36 found that older adults with lower limb amputation used assistive devices with greater frequency than those with either a stroke or orthopaedic deficit.…”
Section: Discussionmentioning
confidence: 99%